Predictive value of National Institutes of Health Stroke Scale combined with serum high-sensitivity C-reactive protein at admission to ischemic stroke - YUAN Li; ZHANG Jian-xing; WANG Su-jie; CHEN Fei-fei; HE Xiao-hong; CHEN Li-li (Chinese Journal of Contemporary Neurology and Neurosurgery, 2022)
Objective To investigate the predictive value of the National Institutes of Health Stroke Scale (NIHSS) score combined with serum high-sensitivity C-reactive protein (hs-CRP) on admission to ischemic stroke. Methods A total of 487 patients with acute ischemic stroke admitted to the Department of Neurology of Tangshan Gongren Hospital from May 2018 to December 2019 were selected. The clinical data of patients were collected such as gender, age, hypertension, diabetes, coronary heart disease, previous stroke history, smoking and drinking history, serum low-density lipoprotein cholesterol (LDL-C), total cholesterol (TC), triglyceride (TG), hs-CRP, homocysteine (Hcy), fasting blood glucose (FBG). The NIHSS scale was used to evaluate the degree of neurological deficit at admission, and the modified Rankin Scale (mRS) was used to evaluate the prognosis when the patient was discharged. The mRS score ≤ 2 was defined as good prognosis, and the mRS score > 2 was defined as poor prognosis. Univariate and multivariate forward Logistic regression analysis were used to screen risk factors for poor prognosis of ischemic stroke, and the receiver operating characteristic (ROC) curve was used to compare the predictive value of NIHSS and hs-CRP levels at admission alone or in combination for patient prognosis. Results Compared with the good prognosis group, the poor prognosis group had higher proportions of male patients (χ2 = 4.729, P = 0.030), previous history of stroke (χ2 = 13.665, P = 0.000), and drinking alcohol (χ2 = 8.326, P = 0.004). The NIHSS score at admission (Z = -9.316, P = 0.000), serum FBG (Z = -3.234, P = 0.001), Hcy (Z = -3.652, P = 0.000) and hs-CRP (Z = -8.780, P = 0.000) level in poor prognosis group were higher than those in good prognosis group. Logistic regression analysis showed that the NIHSS score increased at admission (OR = 1.316, 95%CI: 1.223-1.417; P = 0.000), and the serum hs-CRP level increased (OR = 1.045, 95%CI: 1.032-1.058; P = 0.000) were risk factors for the prognosis of ischemic stroke. The area under the curve (AUC) predicted by the two combined (AUC = 0.903; 95%CI: 0.873-0.928, P = 0.000) exceeded than that of the NIHSS score at admission alone (AUC = 0.818; 95%CI: 0.781-0.852, P = 0.000) and the serum hs-CRP alone (AUC = 0.806; 95%CI: 0.768-0.840, P = 0.000); pairwise comparison found that the combination of the two was better than the NIHSS score at admission alone (Z = 3.187, P = 0.001) and serum hs-CRP alone (Z = 4.418, P = 0.000). Conclusions NIHSS score and high level of serum hs-CRP at admission are risk factors for poor prognosis of ischemic stroke. Combining NIHSS score and serum hs-CRP can provide an effective reference for clinical prediction of poor prognosis of ischemic stroke.